Sustainable Tourism Development Based on Local Wisdom in Sutojayan Village, Malang Regency: A Participatory Approach in Masterplan Planning - Isnandar Isnandar; Joko Samodra; M. Aris Ichwanto; Wahyu Sakti Gunawan Irianto; Salsabila Thifal Nabil Haq; Rian Syahmulloh Hendranawan; Luhur Adi Prasetya; Amir Rofiudin (Universitas Negeri Malang, 2025)
This research and service aims to develop a sustainable tourism masterplan based on local wisdom in Sutojayan Village, Malang, using the Participatory Rural Appraisal (PRA) approach. Observation, in-depth interviews, focus group discussions (FGDs), and questionnaires were conducted to identify natural and cultural tourism potential, infrastructure readiness, and community interest in participating. The results showed that the village has strong tourism attraction, with natural beauty and local traditions as the main assets. Community participation in tourism development is high, especially through micro-enterprises that support the local economy. However, limited infrastructure and concerns about the impact of tourism on local culture are challenges that need to be addressed. The masterplan includes the development of natural tourism zones, culture, creative economy, supporting infrastructure, and tourist information centers. Collaboration with government and external stakeholders is essential to support infrastructure development and destination promotion. Key recommendations include infrastructure improvements, regulations for cultural protection, MSME assistance, and periodic evaluation of tourism impacts. This masterplan is expected to improve the economic welfare of the village while preserving the culture and environment, making Sutojayan Village a model of sustainable tourism destination based on local wisdom.